Belief in a just world and well-being of bullies, victims, and defenders: a study with Portuguese and Indian students - Correia, I. (2017)
Previous findings characterize the belief in a just world (BJW) as a valuable resource for maintaining positive well-being and assimilating injustice. The present cross-sectional study applies just world research to school bullying and tested the hypotheses that the personal BJW is positively correlated with subjective well-being, here particularly school distress. In this paper the generalizability of this association is tested in victims, bullies, and defenders, and across gender and also two countries with different cultures, Portugal and India. We will test if BJW can best be interpreted as a personal resource (main effect) or a buffer (moderator) for the distress of victims, bullies and defenders of the victims. The participants were 465 school students (Portuguese sample: 187 students aged between 12 and 18 years; Indian sample: 278 Indian students aged between 14 and 17 years). Overall, the results of the study supported the personal resource hypothesis. The stronger the adolescents' endorsements of the BJW the less they felt distressed at school, and this was true independent of their bullying behavior and within both sexes and across both samples, although boys, bullies, and Portuguese adolescents experienced more distress and defenders experienced less distress at school.